Bridging National and Islamic Criminal Law in Addressing Online Gambling: A Criminological Case Study from Deli Serdang - Muhammad Saropi Satria Komba; Rajin Sitepu (Universitas Islam Negeri Alauddin Makassar, 2025)
The advancement of internet infrastructure and digital services has facilitated easier access to online gambling, including in Deli Serdang Regency, North Sumatra. This study aims to analyze the regulation of online gambling under national criminal law and Islamic criminal law, as well as to examine the social phenomena surrounding offenders in the region. The research employs a juridical-empirical approach, combining a literature review of relevant laws and academic works with interviews involving stakeholders and online gambling offenders. The findings reveal that most offenders are male, aged 18–35, from lower-middle economic backgrounds, and access online gambling platforms via mobile devices. The primary motivations include the pursuit of instant financial gain and the desire to escape life pressures. The impacts encompass family financial losses, psychological stress, and the potential involvement in other criminal activities. Under national criminal law, online gambling constitutes a prohibited offense subject to criminal sanctions, whereas under Islamic criminal law, it is subject to ta‘zīr punishments determined by the government or judicial authorities. Law enforcement at the local level remains limited due to inadequate digital monitoring and public awareness efforts. The study recommends enhancing synergy between local governments, law enforcement agencies, educational institutions, and religious leaders through education programs, digital monitoring, strict enforcement of sanctions, and social assistance for vulnerable individuals.